Creating and disseminating coach education policy: a case of formal coach education in grassroots football. Issue 8 (13th October 2021) - Dempsey, Noel M.; Richardson, David J.; Cope, Ed; Cronin, Colum J.
ABSTRACT: By examining on-course pedagogical practices, recent research has sought to inform the development of National Governing Body (NGB) coach education courses. Coach education programmes are, however, social constructs, and are influenced by policies and socio-economic factors. To inform future provision, there is a need to understand the construction of policy and the influences affecting course design. This study examined how the English Football Association (FA) redeveloped their coach education policy in 2016. The 2016 changes are pertinent because calls for educational provision to be informed by social constructivism have been made. The FA's coach education policy (2016) claim to be informed by such a philosophical stance. This study, therefore, reports on what policy was created, and how it had been disseminated within the organisation. Twenty-eight interviews were conducted with 14 participants (staff members with different roles within the FA) across two separate points in time, 12 months apart. A thematic analysis identified three key themes: (1) Three Elements of Curriculum/Course Design (A learning strategy informed by social constructivism; a body of content for courses; a coaching competency framework and qualification specification); (2) Recontextualisation of the policy and some confusion during dissemination; and (3) A restricted code when disseminating policy. The significance of these findings extends beyond the case presented and policy makers who seek to inform course design with learning theory may wish to offer elaboration throughout the workforce via text and discourse. Future research should build on these findings and consider how knowledge is selected and legitimised by policy makers, and how coach developers implement recontextualised policies.